Information Processing in Accordance with the Rule of Cerebrovascular Mid-Term and Their Relationship to the Level of Performance of Some Scouting Skills for Studies - Aqeel Yahya Hashim Abdulaziz (Journal of Global Pharma Technology, 2016)
The study of the mental and physiological aspects of the player and learner by the teachers and trainers today has become of great importance. The interest in the study of information processing and treatment levels has emerged as one of the types of learning that has to do with the individual learner himself and to guide him self-directed towards learning by drawing on his knowledge and there is a close connection and according to the type of mental sovereignty or the dominant style of thinking of the athlete whether he has cerebral dominance in the right half or left or there is integrated between the functions of the two halves, and recent years have seen a remarkable interest in the study And the importance of identifying the differences between the two halves of the brain, which contribute to the identification of many things related to human behavior and learning Scouting skills.The researchers followed the following steps in the research procedures:The descriptive approach was used in the method of interconnectivity.The study was conducted on the students of the first stage in the Department of Physical Education College of Education for Girls - University of Kufa for the academic year 2017-2018 The sample (33)The sample was divided according to the test of brain sovereignty to three groups represented the first group (right half), the second group represented (left half), and the third group represented (integrated system).The research requires the use of several tests, including the following:Information processing test.Test the level of information processing systems (right half, left half, integrated system).Skillful skill tests (nodular node, horizontal node).The results of the research:The level of information processing and accuracy of horizontal node performance of the right-hand system is better than those of the left and integrated system.The level of processing information undermining the tent for the right-wing system is better than those of the left and integrated system.Information processing is an important and essential role for people with right, left and integrated systems and the performance of horizontal node and node nodes.Keywords: Information processing, Cerebral dominance, Temporal node and horizontal node.